Oscillating between structure and communitas: A model of ecumenical theory and practice following Victor Turner Oszillieren zwischen struktur und communitas: Ein modell ökumenischer theorie und praxis im anschluss an victor turner - Teuchert, Lisanne (Evangelische Theologie, 2019)
Thirty years ago, the first German translation of Victor Turner's»The Ritual Process: Structure and Anti-Structure« was published. Since then, it has had a wide influence, amongst others, in Practical Theology. But also for interpreting the current ecumenical situation, Turner's theory of ritual has great potential. In this essay, this situation is interpreted with Turner's concept of liminality which oscillates between structure and anti-structure or communitas. From this point of view, there is no unfortunate gap between the ecumenism of doctrinal consensus and the ecumenism of experience. Rather, both are part of a necessary dialectical process oscillating between structure (denomination, doctrine, office) and communitas (experienced community of unity). Within this»phase change«, ecumenism remains both stable and innovative.
CRIS-Team Scopus Importer:2024-09-30
Keywords: Systematische Theologie; Dogmatik; Ökumenische Theorie; Victor Turner